Pengaruh Living Values Education Program Terhadap Penguatan Karakter Religius Pada Siswa Kelas V SD 3 Pengalusan - Wahyu Hidayana; An-Nisa Apriani (Indonesian Journal of Elementary Education and Teaching Innovation, 2023)
This study aims to determine the effect of the living values education program (LVEP) learning model on strengthening religious character in students. This research is a quasi-experimental study with a pre-test pos-test control group design. The research subjects were students of class V SD 3 Pengalusan, Purbalingga. The sample was selected based on random sampling for students using the Living Values Education Program learning. The instrument used in this study was an observation sheet to measure students' religious character. The data that has been collected is then analyzed using the t test. the results of the study showed that there were differences in religious character in learning between students who used the living values education program model in learning to have a higher level of religious character compared to students who used the expository learning model.Keyword: LVEP, Religious, Elementary Students